2020
DOI: 10.1212/wnl.0000000000008844
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of periodic limb movements in OSA and the effect of CPAP therapy

Abstract: ObjectiveWe sought to assess the prevalence, correlates, and consequences of periodic limb movements of sleep (PLMS) in persons with obstructive sleep apnea (OSA) and the effect (worsening or improvement) of continuous positive airway pressure (CPAP) therapy on PLMS in a large prospective multicenter randomized controlled trial.MethodsWe performed retrospective analyses of data from the Apnea Positive Pressure Long-term Efficacy Study, a prospective multicenter randomized controlled trial. A total of 1,105 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
3
24
2
Order By: Relevance
“…1 The incidence of PLMS increases with age and is associated with several predisposing medical conditions, including narcolepsy, Parkinson’s disease, idiopathic REM sleep behavior disorder, and diabetes mellitus. 3 Though there appears to be no clear link between PLMS and excessive daytime sleepiness, 4 , 5 PLMS has been reported to be associated with poorer sleep quality, 6 arousals 7 , 8 and possibly sleep fragmentation 4 and increased risks of cardiovascular diseases. 9 PLM is also observed in 80% of patients with restless legs syndrome (RLS) 10 and 24–48% of patients with Obstructive Sleep Apnea (OSA).…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence of PLMS increases with age and is associated with several predisposing medical conditions, including narcolepsy, Parkinson’s disease, idiopathic REM sleep behavior disorder, and diabetes mellitus. 3 Though there appears to be no clear link between PLMS and excessive daytime sleepiness, 4 , 5 PLMS has been reported to be associated with poorer sleep quality, 6 arousals 7 , 8 and possibly sleep fragmentation 4 and increased risks of cardiovascular diseases. 9 PLM is also observed in 80% of patients with restless legs syndrome (RLS) 10 and 24–48% of patients with Obstructive Sleep Apnea (OSA).…”
Section: Introductionmentioning
confidence: 99%
“…Transient hyperventilation response after awakening causes blood CO levels to continue to decline after the end of apnea events, aggravating ventilatory instability and perpetuates the cycle of repetitive arousals, leading to sleep disruption 17,32 . Indeed, this mechanism of low arousal threshold could offer an explanation for the increased arousals and reduced sleep e ciency in OSA-PLMS patients seen in some studies 6,7 , bridging the gap between the ostensibly unrelated symptoms of PLMS and OSA. Crucially, this negative effect is further compounded by the more recent nding that put into doubt the traditional belief that arousals are necessary for re-opening of the obstructed airway 18,33 , that is, arousals are not a "protective" mechanism as traditionally suggested and low ArTH contributes to the pathogenesis of severe OSA 34 .…”
Section: Multivariate Logistic Regressionmentioning
confidence: 94%
“…Evidently, the underlying link between PLMS and a whole host of comorbidities warrant further investigation into this clinical disorder, despite its lack of frank clinical symptoms. In PLMS patients who are often treated by CPAP for their concomitant OSA, studies have shown that CPAP treatment has no clear impact on the severity of PLMS 6,13 . The current treatment approaches of PLMS mainly "borrow" from the pharmacological treatments of RLS, where the current guideline presents a "standard" level of recommendation for pramipexole and ropinirole and a "guideline" level of recommendation for levodopa with dopa decarboxylase inhibitor, opioids, gabapentin enacarbil in the treatment of RLS 45 .…”
Section: Clinical Signi Cancementioning
confidence: 99%
See 2 more Smart Citations